The use of hemodynamic and cerebral monitoring to study pharmacodynamics in neonates (2017)
Background: Drugs acting on the cardiovascular and central nervous system often display relatively fast clinical responses, which may differ in neonates compared to children and adults. Introduction of bedside monitoring tools might be of additional value in the pharmacodynamic (PD) assessment of such drugs in neonates. Methods: We aim to provide an overview of the frequently used monitoring tools to assess drug effects on the hemodynamic status as well as the cerebral circulation, oxygenation and cerebral metabolism in neonates. Results: The use of blood pressure measurements, heart rate variability, functional echocardiography, nearinfrared spectroscopy and (amplitude-integrated) electroencephalography in neonates is discussed, as well as new parameters introduced by these tools. Based on the ‘brain circulation model’, the hemodynamic effects on the brain and their interplay are summarized. In this model, 3 processes (i.e. blood processes, vascular smooth muscle processes and tissue processes) and 3 mechanisms (i.e. autoregulation, blood flow metabolism coupling and cerebral oxygen balance) are distinguished, which all may be influenced by drug administration. Finally, propofol, sevoflurane, midazolam and inotropes are used as examples of which PD has been studied using the available hemodynamic and/or cerebral monitoring tools. Conclusion: The implementation of (non-)invasive monitoring tools to document hemodynamic and cerebral PD effects in neonates is of relevance both in a neonatal research and intensive clinical care setting. We highlight the need to integrate these tools in future PD research. Furthermore, besides short-term drug effects, long-term outcome of drug therapy in neonates also warrants further attention.